Chemically stable microporous hyper-cross-linked polymer (HCP): an efficient selective cationic dye scavenger from an aqueous medium. (1st March 2017) - Samanta, Partha; Chandra, Priyanshu; Desai, Aamod V.; Ghosh, Sujit K.
Abstract : Charge-selective capture of organic cationic dye molecules (water pollutants) from an aqueous medium has been demonstrated using a cost-effective and stable microporous hyper-cross-linked material (HCP-91@Na ). Abstract : A cost-effective and robust microporous hyper-cross-linked organic material (HCP-91 ) has been post-synthetically modified for the rational incorporation of sodium cations via alkali treatment (HCP-91@Na ). The presence of free cations has been tapped for the selective capture of cationic dyes via rapid ion-exchange. For this study we have used three cationic dye molecules [namely, methylene blue (MB), crystal violet (CV) and rhodamine B (RB)] and one anionic dye (methyl orange). The performance ofHCP-91@Na in an aqueous medium for size and charge-selective dye entrapment has been comprehensively investigated with monocomponent dye solution studies, as well as binary mixtures of cationic and anionic dye molecules.